Newman and Scaffolding Stages in Analyzing Student Errors in Solving Algebraic Problems - Rachmawati, Lelly Nur; Sah, Retno Wahyu Arian; Hasanah, Siti Nur; Hazarika, Anurag (CV. Bimbimbingan Belajar Assyfa, 2023)
Algebra is a branch of mathematics that is abstract in form so that students do errors in solving problems of Algebra. The purpose of this research is to describe: (1) the errors form made by students in solving algebraic operation story problems based on the Newman stage, (2) the scaffolding form given to students who make errors in solving problems of algebraic form operations. This research is a qualitative descriptive with research subjects of 3 students of class VIII at MTs Unggulan Singa Putih. The results of the study state that: (1) the errors form on the reading step is students cannot read the problems by beheading or stopping correctly, on the comprehension step the students do not know the meaning of the problem, on the transformation step the students cannot modelling variables appropriately, on the process skill step the students unable to perform operation of algebraic forms appropriately, on the encoding step the students cannot answer correct conclusions, (2) the scaffolding forms given to students is students are requested to recheck or reread the results of their work, students are given questions that lead students to think more about the problem, and give praise to motivate students to improve their work.